Forty Years of Scientific Instrument Studies : The Scientific Instrument Commission - Kremer, Richard L.,; Schechner, Sara J., (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
Since 1981, the Scientific Instrument Commission has provided a forum for annual international discussion of topics close to the hearts of those caring for and researching historic scientific instruments. During these years, increasing professionalisation of curatorship and deepened engagement by historians have led to important changes in these roles. This volume is a cornucopia illustrating how instrument studies have changed and flourished over the past forty years. Four chapters review the work of the Scientific Instrument Commission by decade. The remaining chapters consider the historiography of instrument studies, the cataloguing of collections, historic instruments in exhibitions and educational settings, national trends, and the impact of new media. This book includes twenty smaller, in-depth "Fingerposts", or colourfully illustrated vignettes, presenting significant artefacts selected to span the spread of historical instrumentation through time and geography. They demonstrate the variety of historical questions and thematic analyses that can be explored through close inspection of particular scientific instruments. Contributors are R.G.W. Anderson, Sara J. Schechner, Richard L. Kremer, David Pantalony, Boris Jardine, A.D. Morrison-Low, Giorgio Strano, Jean-François Gauvin, Sofia Talas, Pedro Raposo, and Floor Koeleman.